Wake development in floating wind turbines: new insights and an open dataset from wind tunnel experiments - A. Fontanella; A. Fusetti; S. Cioni; F. Papi; S. Muggiasca; G. Persico; V. Dossena; A. Bianchini; M. Belloli (Wind Energy Science, 2025)
Floating offshore wind turbines represent a promising advancement in renewable energy, yet they remain in early development stages with limited performance data. As part of the NETTUNO research project, this study investigates how platform motion affects the aerodynamics of a floating wind turbine rotor and connects its load response to the wake evolution. Wind tunnel experiments were conducted using a 1:75-scale wind turbine model subjected to platform motions in various directions. Measurements include rotor loads and wake velocities at downstream distances from 3 to 5 rotor diameters. The results show that surge and pitch motions induce periodic thrust fluctuations, leading to significant variations in near-wake velocity, that have maximum amplitude at a reduced frequency of 0.6. Yaw motion causes oscillations in yaw moment and lateral wake meandering, while combined surge and sway motions result in skewed apparent wind, causing both wake velocity fluctuations and lateral meandering. Increased turbulence intensity near the wake center suggests enhanced mixing and potentially faster wake recovery beyond 5 rotor diameters, which is the furthest distance examined in the experiment. This new experimental dataset serves as a foundation for validating numerical simulation tools and provides valuable insights for optimizing the design and layout of future large-scale floating wind farms.